(untitled) (Al-Academy, 2024)
The technological development in the elements of the production of the theatrical image is related to several vocabulary that is employed in drawing the theatrical landscape, which is directly related to the place, as the mechanism of functioning of the scenography in the children’s theater is formed through the system of light with its various devices, visual effects and advanced techniques, as the quantitative and qualitative presence of these two elements can be preceded by technical knowledge that allows defining the art of synchronization and the art of installation, that is, in the sense that each decorative piece must be in its actual place, and its functioning accompanies the functioning of movement and action, until it is completed. Activate this decorative piece and not leave it inactive."This is achieved through the paths of light movement resulting from the techniques of installing light in the theatrical show, whether in local movement and changing the sources of light spots, or by using follow-up devices, lasers, or all available kinetic means of light." (Al-Bahli, 2010, p. 195)Also, the visual elements that contribute to presenting scenographic features for the show must be concerned with the temporal sequence associated with the spatial sequence, and they form the pattern of events, the movement of the characters of the play, the nature of the conflict and the relations between the characters on the one hand and between the characters and the show space on the other hand.The concept of building or structure, which has come to mean “how a group of coherent elements are organized among themselves, so that each element depends on the rest of the other elements, and this element is determined by its relationship to those elements” (Benabd Al-Aali, 2005: 11).Therefore, the visual systems and their educational connotations can appear in the performances of the child’s theater so that they constitute one of the most important starting points on which the space of the theatrical performance is based, being an integral part of the sensory perceptions that contribute to achieving entertainment and enjoyment in a dramatic manner that the child can comprehend. Positivity and work to change or consolidate his concepts and the constancy of acquired social values and habits, so the visual formats play their role in the space of the child’s theater because they perform their function in two ways, the first is towards the visual formats and the mechanism of its operation educationally, and the second is the mechanism of work and its relationship to the scenography of the child’s theater.